The Multifaceted Influence of Financial Literacy and Education on SME Financing Decisions in Different Economic Contexts - Ciptawan Ciptawan (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
This research delved into the multifaceted impact of financial literacy and education on Small and Medium-sized Enterprises (SMEs) financing decisions across diverse economic contexts. A systematic literature review examined 280 papers from top-tier "small business management" journals between 1986 and 2020. The analysis unveiled a complex relationship between financial literacy dimensions, such as numerical literacy, risk perception, product understanding, and SME financing choices. Financial education programs emerged as vital tools, increasing awareness of financing options, improving credit application procedures in the short term, and fostering improved decision-making capabilities and long-term financial resilience. The study further highlighted how contextual factors, including cultural norms, regional economic variations, and access to resources, significantly shaped the outcomes of financial education interventions. Additionally, the evolving landscape of digitalization and fintech adoption introduced new dynamics, with financial literacy proving essential for effectively utilizing digital financial tools. These findings underscore the critical role of financial literacy and education in empowering SMEs to make informed financing decisions, navigate challenges, and seize growth opportunities across diverse economic landscapes. Keywords — financial literacy, financial education, SME financing decisions, economic contexts, contextual factors, digitalization, fintech adoption